Occlusion of dentinal tubules on periodontally involved teeth by dentifrice containing stannous fluoride and sodium fluoride - (:unkn) unknown (My University, 2023)
Purpose: This study examined the occlusion effect of a dentifrice containing stannous fluoride (SnF2) and sodium fluoride (NaF) on periodontally involved teeth in comparison with healthy teeth using scanning electron microscopy (SEM) in comparison with a dentifrice containing NaF alone. Methods: Sixty dentine samples obtained from single-rooted premolars, 15 of them extracted for orthodontic reasons (Group H) and 15 because of periodontal destruction (Group P), were included in the study. Each group of specimens was further divided into subgroups: HC and PC (control), H1 and P1 (treated with SnF2 and NaF), and H2 and P2 (treated with NaF). The samples were brushed twice a day for 7 days, kept in artificial saliva, and examined by SEM. The diameters of open tubules and the numbers of tubules were assessed at ×2,000 magnification. Results: The H and P groups showed similar diameters of open tubules. The numbers of open tubules in Groups H1, P1, H2, and P2 were significantly lower than in Groups HC and PC (P < 0.001), and consistent with the percentages of occluded tubules. Group P1 had the highest percentage of occluded tubules. Conclusions: Although both dentifrices were found to successfully occlude dentinal tubules, the dentifrice containing SnF2 and NaF provided the highest degree of occlusion in periodontally involved teeth.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; dentifrice; dentine hypersensitivity; occlusion; scanning electron microscopy; stannous fluoride